ANALISIS FRAMING PADA PEMBERITAAN PARTAI PERINDO DI SINDONEWS.COM DALAM PUTARAN KEDUA PILGUB DKI 2017 - Waluyan, Elsa Engelina; Amanda Gelgel, Ni Made Ras; Pradipta, Ade Devia (E-Jurnal Medium, 2018)
ABSTRA CT   The online media have many advantages in delivering news to audiences by directing public awareness to issues that are considered important through the agenda setting process. One aof the aissues that developed in the amass media was about the Partai Perindo support for the Anies-Sandi in the second round of the DKI Jakarta Governor Election in 2017. One of the online media reporting on Partai Perindo support for the Anies-Sandi  was Sindonews.com online media. This research was aconducted to afind out the framing of the Partai Perindo  support for the Anies-Sandi at Sindonews.com by analyzing the news that was published from March 9 to April 21, 2017. This aresearch was a aqualitative research using the framing analysis amethod of Zhongdang aPan and Gerald aM.Kosicki . The results of this astudy indicate that Sindonews.com is very much in favor of the interests of the media owner, Hary Tanoesoedibjo, who is also the Chair of the aParty in the production and distribution activities of reporting the Partai Perindo  support for the Anies-Sandi in the second round of the DKI Jakarta Governor Election in 2017. In framing the news there are four fractions that the author finds. It is also seen in the setting agenda process that Sindonews.com forces the public to pay attention to issues regarding the Partai Perindo support to the Anies-Sandi so that it influences people's thinking to participate in choosing Anies-Sandi through words or sentences that are presented repeatedly. Keywords: Framing Analysis, Partai Perindo News at Sindonews.com, Political Economy of Media, Agenda Setting